Organic Chemistry - McMurry, John E. (Open textbook library., 2023)
John McMurry's Organic Chemistry is renowned as the most clearly written book available for organic chemistry. In John McMurry's words, "I wrote this book because I love writing. I get great pleasure and satisfaction from taking a complicated subject, turning it around until I see it clearly from a new angle, and then explaining it in simple words." In Organic Chemistry: A Tenth Edition from OpenStax, McMurry continues this tradition while updating scientific discoveries, highlighting new applications, scrutinizing every piece of art, and providing example problems to assist students. Organic Chemistry: A Tenth Edition continues to meet the scope and sequence of a two-semester organic chemistry course that follows a functional group approach. A highlighted list of changes along with a detailed table of contents and ancillary descriptions can be found on the Instructor and Student resources sections of this page. John McMurry decided to publish Organic Chemistry: A Tenth Edition under an open license as a tribute to his son, Peter McMurry, who passed away from cystic fibrosis in December 2019. Please click here to learn more about Peter's legacy and to support the fight against cystic fibrosis.